The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1029/2010jb007609
|View full text |Cite
|
Sign up to set email alerts
|

Helium isotope variations between Réunion Island and the Central Indian Ridge (17°–21°S): New evidence for ridge–hot spot interaction

Abstract: [1] We report new helium abundance and isotope results for submarine basaltic glasses from the Central Indian Ridge (CIR) between the Marie Celeste (16.7°S) and Egeria fracture zones (FZ) (20.6°S); the adjacent Gasitao, Three Magi, and Rodrigues ridges; and for olivine separates from lavas and cumulate xenoliths from the Mascarene Islands (Réunion, Mauritius, and Rodrigues). Helium isotope ratios in basaltic glasses range from 7.1 to 12.2 R A (where R A = air 3 He/ 4 He) and lie between values of Mid-Ocean Rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
71
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 90 publications
9
71
0
Order By: Relevance
“…They proposed that the geochemical variations of zero-age basalts may primarily reflect periodic processes rather than the spatial distribution of mantle heterogeneities. Füri et al (2011) reported significantly higher 3 He/ 4 He rations between 19 and 20 along the axis, as well as along the Gasitao Ridge, Three Magi Ridges and Rodrigues Ridge, consistent with lateral flow of hot spot mantle from Reunion toward the CIR. However, basaltic lavas sampled at CIR-15B axis, i.e., the intersection of the CIR and the off-axis volcanic structures, show typical N-MORB-like trace element ratios.…”
Section: Rock Geochemistrymentioning
confidence: 49%
See 1 more Smart Citation
“…They proposed that the geochemical variations of zero-age basalts may primarily reflect periodic processes rather than the spatial distribution of mantle heterogeneities. Füri et al (2011) reported significantly higher 3 He/ 4 He rations between 19 and 20 along the axis, as well as along the Gasitao Ridge, Three Magi Ridges and Rodrigues Ridge, consistent with lateral flow of hot spot mantle from Reunion toward the CIR. However, basaltic lavas sampled at CIR-15B axis, i.e., the intersection of the CIR and the off-axis volcanic structures, show typical N-MORB-like trace element ratios.…”
Section: Rock Geochemistrymentioning
confidence: 49%
“…CIR-S15 and S16, sometimes known as the Rodrigues Segment (RS), are sandwiched between the Egeria and Marie-Celeste Fracture Zones and both the on-and off-axis areas are shallower than the adjacent normal segments. The unusual elevated and smooth bathymetry, and the geochemical and geophysical characteristics, suggest a hotspot influence on ridge processes, although the Reunion hotspot is presently located 1,000 km away from the CIR (Mahoney et al 1989;Murton 2005;Nauret et al 2006;Füri et al 2011). The Rodrigues Ridge, an WNW-ESE trending volcanic feature (Fig.…”
Section: Regional Settingmentioning
confidence: 99%
“…He-isotopes -the canonical tracer of mantle plume involvement in petrogenesis -are higher (>9 R A ) than typical DMM values of 8 ± 1 R A (where R A = air-like 3 He/ 4 He) at Réunion Island and along the off-axis ridges. In contrast, the CIR exhibits DMM-like 3 He/ 4 He values along axis, except at the point where the projection of the submarine ridges meets the ridge axis ~19.9 °S (Füri et al, 2011;Fig. S-1).…”
mentioning
confidence: 99%
“…The highest and lowest values are -0.10 and -3.8 ‰ giving an on-axis δ 15 N mean value of -2.1 ± 1.1 ‰ (1σ; n = 7) or -1.7 ± 1.6 ‰ (n = 8 if D9-2 is included). Notably, sample D9-2 has a 3 He/ 4 He ratio (7.25 R A ), which falls in the nominal DMM range (8 ± 1 R A ; Graham, 2002) characteristic of most samples on the CIR ridge-axis (Füri et al, 2011). The only on-axis sample (DR10-1) of the present sample suite with a 3 He/ 4 He value higher than DMM ( 3 He/ 4 He = 10.31 R A ) is from the region where the projection of the off-axis ridge impinges the spreading centre (~19.9 °S): it has a δ 15 N value of -0.10 ‰ -the second highest value of the on-axis samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation